Iliac Crest Bone Block Autograft Transfer for Ballistic Posterior Glenoid Fracture: A Case Report - Jordan Cook Serotte; Hayden Baker; Cody Lee; Jason A. Strelzow (Case Reports in Orthopedics)
Conclusion: There is limited consensus on the operative management of ballistic intra-articular fractures due to the heterogeneity of these injuries. Acute posterior glenohumeral instability secondary to a ballistic fracture is a rare injury pattern. In this case, we were able to successfully treat posterior glenohumeral instability with iliac crest autograft transfer and open reduction internal fixation.